A Hybrid Acceptor‐Modulation Strategy: Fluorinated Triple‐Acceptor Architecture for Significant Enhancement of Electron Transport in High‐Performance Unipolar n‐Type Organic Transistors (Adv. Mater. 8/2023). Issue 8 (24th February 2023) - Shen, Tao; Li, Wenhao; Zhao, Yan; Wang, Yang; Liu, Yunqi
Abstract : Organic Transistors In article number 2210093, Yan Zhao, Yang Wang, Yunqi Liu, and co‐workers demonstrate a hybrid acceptor‐modulation strategy to synthesize an acceptor unit with a fluorinated triple‐acceptor architecture (DPP–difluorobenzothiadiazole–DPP (DFB)). The DFB‐based semiconducting polymers feature low‐lying frontier molecular orbital levels, shape‐persistent backbones, and high crystallinity, leading to an electron mobility of up to 5.04 cm 2 V −1 s −1 in unipolar n‐type transistors, which is the highest electron mobility among DPP‐based unipolar n‐type polymers.